Evalueringskriteria en die interaksie tussen die leksikografieteorie en -praktyk; die ontwerp van die Woordeboek van die Afrikaanse Taal as gevallestudie - Swanepoel, P.H. (Lexikos, 2014)
Evaluation criteria and the interaction between lexicographic theory and practice; the design of the Woordeboek van die Afrikaanse Taal as case study. The compilers of the various volumes of the WAT have relied on input from various co-workers, of which dictionary reviewers form an important group. However, a common problem with the evaluation of dictionaries of various kinds (cf. Nielsen 2006, 2009 and Swanepoel 2008, 2013) is that reviews only provide an analysis and description of the design features of dictionaries and not also an evaluation based on a set of clearly formulated and motivated criteria for the evaluation of dictionaries. This problem, the distinction between criteria for the description and evaluation of the design features of dictionaries, and the content, structure and operationalization of lexicographic evaluation criteria, are discussed in this article, taking especially Feinauer (2007), Gouws (2007, 2011, 2014), Gouws and Prinsloo (2005), Nielsen (2006, 2009) and Svensén (2009) as point of departure. Finally, this lexicographic problem is discussed with reference to the design features of WAT Volume XIV.